In situ growth of zeolitic imidazolate framework-8 on a GO–PVDF membrane as a sorbent for thin-film microextraction of caffeine followed by quantitation through high-performance liquid chromatography. Issue 13 (17th March 2020) - Jafari, Zahra; Hadjmohammadi, Mohammad Reza
Abstract : In the present study, the applicability of ZIF-8/LDH/GO/PVDF as a sorbent for the thin film microextraction (TFME) method is introduced. Abstract : In the present study, the applicability of ZIF-8/LDH/GO/PVDF as a sorbent for the thin film microextraction (TFME) method is introduced. The TFME method followed by high-performance liquid chromatography-ultraviolet detection (TFME-HPLC-UV) was applied for the rapid extraction and determination of caffeine (as a model analyte) in various caffeine beverages and urine samples. Parameters that affect the extraction of caffeine were optimized in two consecutive steps as follows: first, a Plackett–Burman Design (PBD) was utilized to screen the significant factors. Then, the screened factors were optimized by utilizing Box–Behnken Design (BBD). Under the optimized conditions (extraction time = 20 min, stirring rate = 665 rpm, salt effect = 20% w/v, 100 μL of methanol and desorption time = 2 min), the method showed good linearity in the ranges of 0.1–200 μg L −1 and 0.2–200 μg L −1 for caffeine in water and urine samples, respectively. The determined coefficients of determination ( R 2 ) were higher than 0.9968. Relative standard deviations (RSDs) for intra-day precision of caffeine at 10 μg L −1 were 4.8% and 5.1% in water and urine samples, respectively. Finally, the method was successfully utilized for preconcentration and measurement of caffeine in various caffeine beverages and urine samples.